Dimensi Akhlak Dalam Berorganisasi: Perspektif Warga Pergerakan PC PMII Jombang - Muhammad Najihul Huda; Amir Maliki Abitolkha; Abd. Mannan (Arsy : Jurnal Studi Islam, 2022)
This article discusses the Dimensions of Morals in Organization for the members of the Jombang PMII movement. This study aims to determine the objective condition of the morals of PMII Jombang members, the form of implementation, and the process of moral formation, to determine the supporting and inhibiting factors in implementing moral values. The type of research conducted is descriptive qualitative research. The approach used in this research is the Theological-Normative approach, Psychological approach. Data were collected through observation, interviews, and documentation. The data obtained were then analyzed descriptively. In this study, the results showed that the moral dimensions contained in the members of the PC PMII Jombang movement varied. There are indicators of good morals but there are also indicators of bad morals. But in practice, there are more good morals. This is because PC PMII Jombang residents consist of students with different backgrounds. So that the practice of moral values ​​in it also has differences between one cadre and another. This affects the process of moral formation that exists in the citizens of the PC PMII Jombang movement. This shows that the implementation of morals among PC PMII Jombang cadres has a dimensional nuance, there are various kinds of morals that are found.